Multimodality, Digitalization and Cognitivity in Communication and Pedagogy - Sukhova, Natalya V.; Dubrovskaya, Tatiana; Lobina, Yulia A. (Numanities - Arts and Humanities in Progress, 2021)
X, 245 p. 43 illus., 35 illus. in color.